2017
DOI: 10.1088/1361-648x/aa919e
|View full text |Cite
|
Sign up to set email alerts
|

Spin reorientation and disordered rare earth magnetism in Ho2FeCoO6

Abstract: Abstract. We report the experimental observation of spin reorientation in the double perovskite Ho 2 FeCoO 6 . The magnetic phase transitions in this compound are characterized and studied through magnetization and specific heat, and the magnetic structures are elucidated through neutron powder diffraction. Two magnetic phase transitions are observed in this compound -one at T N1 ≈ 250 K, from paramagnetic to antiferromagnetic, and the other at T N2 ≈ 45 K, from a phase with mixed magnetic structures to a sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The materials with such extraordinary, multi-functional properties are gained much more interest due to their attractive, well-to-do physics and panorama for technological device applications [2][3][4]. In the last few decades, people are trying to search for such new multifunctional materials for next-generation spintronic devices [4][5][6][7][8][9][10][11][12][13]. In this regard, the rare earth double perovskite (DP) oxides, A 2 BB O 6 (A = rare earth ions or alkaline ions; B/B = transition metal ions) with rock salt ordered structure are of great importance for their multi-functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…The materials with such extraordinary, multi-functional properties are gained much more interest due to their attractive, well-to-do physics and panorama for technological device applications [2][3][4]. In the last few decades, people are trying to search for such new multifunctional materials for next-generation spintronic devices [4][5][6][7][8][9][10][11][12][13]. In this regard, the rare earth double perovskite (DP) oxides, A 2 BB O 6 (A = rare earth ions or alkaline ions; B/B = transition metal ions) with rock salt ordered structure are of great importance for their multi-functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…On further decrease of temperature at T∼T d intensity of feature B encounters a downturn whereas intensity of A increases. In a previous study [43], cation disordered (Pbnm symmetry) Ho 2 FeCoO 6 double perovskite is found to show significant intensity redistribution in magnetic Bragg's lines at low temperature, which is identified as spin reorientation transition leading to transformation from mixed magnetic structure to single magnetic structure. However, this is not the case for SNMO system, as here single magnetic structure is evidenced for all temperature values below T=T C (discussed later).…”
Section: Irs Ir Matrices In Symbolic Form Basis Vectors Symmetry Oper...mentioning
confidence: 86%
“…The strong coupling between magnetic and electrical ordering is one of the key issues to realize the multifunctional materials for potential applications [1][2][3][4]. In this regard, double perovskites (DP) A 2 BB O 6 (where A is rare earth or alkaline ions, B/B are transition metal ions) with rock salt ordered structure [5] are forming the promising classes of multifunctional materials which exhibit unique physical properties such as near room temperature ferromagnetic insulating ground state, large magneto-dielectric effect (MDE), Griffiths phase, giant exchange bias, low temperature re-entrant glassy states, spin-phonon coupling etc [6][7][8][9][10][11][12][13]. Recently, A 2 CoFeO 6 types 4 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…of DP oxides have gained attention due to their high temperature phase transitions [10]. In fact, Co and Fe ions have their own features as they have similar size and valance states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation